Substitute either equation into the other to solve. I'm going to substitute the second equation for the value of y in the first:

2x + (1/3x +1) = -6

(7/3x) + 1 = -6

7/3x = -7

**x=-3**

**y=0**

The graph plots 2x + y = -6 as blue and y =1/3x +1 as orange

Substitute either equation into the other to solve. I'm going to substitute the second equation for the value of y in the first:

2x + (1/3x +1) = -6

(7/3x) + 1 = -6

7/3x = -7

**x=-3**

**y=0**

The graph plots 2x + y = -6 as blue and y =1/3x +1 as orange